The future is now: how scenarios can help Senegalese and Mauritanian fisheries adapt to climate change - Badjeck, M.C.; Diop, N. (2010)
Localized changes in the productivity of marine and inland waters induced by climate change will pose new challenges to the fishery and the aquaculture sectors in West Africa. However, climate change does not occur in isolation of other drivers of change: processes of environmental, economic and social change can affect the fishery sector, potentially creating additional vulnerability to climate change. Scenarios are a useful tool to explore uncertainties and understand non-climatic drivers of change. Despite their prevalence in global environmental change research, few have focused on the fisheries sector. This article presents the construction of fisheries sector scenarios for Senegal and Mauritania required for the analysis of climate change adaptation policies.